Research progresses and hotspots on glucose metabolic reprogramming in breast cancer: a bibliometric analysis over the past two decades - Huang, Lei; Zhao, Wenyue; Sun, Lamei; Niu, Dong; Zhu, Xiaodan; Jin, Chunhui (Frontiers in Oncology, 2025)
BackgroundAbnormal energy metabolism is a prominent characteristic of cancers. Increasing evidence has suggested the involvement of glucose metabolism reprogramming in the progression of breast cancer (BC). This article aims to provide a comprehensive overview of glucose metabolism reprogramming in BC through a bibliometric analysis.MethodsRelevant literatures published from 2004 to 2024 were searched in the Web of Science Core Collection database, and a bibliometric analysis was conducted using VOSviewer, CiteSpace, and Bibliometrix.ResultsIn total, 957 publications reporting glucose metabolism reprogramming in BC were included, showing an increasing trend in the annual publication outputs. China ranked first in publication outputs, and the United States of America (USA) had a dominant place in citation counts. The research achievements of Thomas Jefferson University in the USA were at the forefront and widely cited. Lisanti, Michael P., and Sotgia, Federica were the most productive authors. Keyword analysis suggested that the mechanisms of glucose metabolism reprogramming in BC and related therapeutic strategies were the research hotspots.ConclusionThis study, for the first time, elucidated the progresses and hotspots of in the research on glucose metabolism reprogramming in BC, highlighting its potential role in treating BC. Considering that the glycolytic reprogramming of BC is a complex biological process, it is imperative for countries to enhance cooperation in the pursuit of effective antimetabolic therapies to overcome challenges in BC treatment.